The role of social media in raising awareness and influencing sunscreen usage in the Western region of Saudi Arabia - Alharbi, Lama K.; Alsulami, Judy K.; Alshehri, Faisal S.; Alsulami, Joury A.; Alsaggaf, Ahmed G.; Alghanemi, Logain G.; Andijani, Fedaa S. (International Journal of Research in Dermatology, 2025)
Background: Ultraviolet (UV) exposure is linked to major dermatological problems such as sunburn, early aging, and carcinogenesis. Sunscreen has beneficial effects, but because of misconceptions and low awareness, global compliance is below ideal. This study is to raise awareness and investigate the influence of social media on sunscreen application, given the high levels of UV exposure in Saudi Arabia’s western region. Methods: A cross-sectional survey is filled out by residents of Saudi Arabia’s western region. Data on demographics, sunscreen use, and social media impact was obtained using a social media questionnaire. Statistical package for the social sciences (SPSS) (version 26) was used for statistical analysis, and the chi-squared test to identify significant relationships between variables. Results: Between the 385 participants, (64.2%) were female, (57.9%) were students, and (67.5%) were between the ages of 19 and 54. (74%) of participants reported exposure to social media content as a factor influencing their use of sunscreen. Instagram and Snapchat users were inclined to wear sunscreen, specifically those watching videos. Additionally, (75.1%) of participants stated that social media raised public awareness about sunscreen use, and (35.3%) of them started applying sunscreen through social media influence. Conclusions: In conclusion, this study demonstrates that social media encourages the use of sunscreen in Saudi Arabia’s western region, with young adults and females engaging more to such campaigns. Successful public health campaigns are advertised by educational and visual contents. Future research should address the utility of these findings and long term behavioural sustainability.